1983
DOI: 10.1021/bi00270a016
|View full text |Cite
|
Sign up to set email alerts
|

Activation of angiotensin converting enzyme by monovalent anions

Abstract: The angiotensin converting enzyme catalyzed hydrolysis of furanacryloyl-Phe-Gly-Gly is activated by monovalent anions in the order C1- greater than Br- greater than F- greater than NO3- greater than CH3COO-. In the alkaline pH region, increasing anion concentrations decrease the KM but do not change the kcat. This behavior is characteristic of an ordered bireactant mechanism in which the anion binds to the enzyme prior to the substrate. At acidic pH values, however, the anion activation is a result of both a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 24 publications
1
45
0
1
Order By: Relevance
“…Since its discovery, ACE was thought to be a metaldependent peptidase because enzymatic activity was virtually totally inhibited by EDTA (Skeggs et al, 1956a;Bünning and Riordan, 1983). The purified enzyme was shown to contain zinc by atomic absorption spectroscopy, and it was estimated (incorrectly) A Modern Understanding of ACE 5 that each molecule of ACE contained only one metal atom (Das and Soffer, 1975;Bünning and Riordan, 1985).…”
Section: Angiotensin-converting Enzyme Substratesmentioning
confidence: 99%
“…Since its discovery, ACE was thought to be a metaldependent peptidase because enzymatic activity was virtually totally inhibited by EDTA (Skeggs et al, 1956a;Bünning and Riordan, 1983). The purified enzyme was shown to contain zinc by atomic absorption spectroscopy, and it was estimated (incorrectly) A Modern Understanding of ACE 5 that each molecule of ACE contained only one metal atom (Das and Soffer, 1975;Bünning and Riordan, 1985).…”
Section: Angiotensin-converting Enzyme Substratesmentioning
confidence: 99%
“…In this regard, the Cl--stimulated cellobiosidase again resembles the arylsulfatase, which showed little change in its pH activity curve when the chloride content was varied (42). Previous studies on anionactivated enzymes appear to point to the presence of two distinct types of activation (7). Bovine lysosomal cathepsin C (18) and Escherichia coli Mg,Ca-ATPase (1) belong to a group of anion-activated enzymes in which anions only affect the K,,,.…”
Section: E E180mentioning
confidence: 93%
“…Only the activation of a-amylase seems to be as effective, and the maximal activity of this enzyme was found at anion concentrations below 5 mM (30). Many other chloride-activated enzymes show their highest activities at relatively high anion concentrations (1,18,38,42 Results of studies on several anion-stimulated enzymes have indicated that activation is accompanied by a shift of the pH activity profile toward the alkaline pH region, presumably because the combination of the anion with a basic group adjacent to a basic iotlizable group at the active site shifts the dissociation constant of the ionizable group toward the alkaline side (7,11,41). This does not seem to apply to the activation of the cellobiosidase.…”
Section: E E180mentioning
confidence: 99%
“…21 n Figure 1 shows that there was a moderate concentration-dependent activation by borate that was demonstrable even in the presence of a near optimal NaCl concentration (0.9 M) at pH 8.3 (see Table 3). Ionic strength has been suggested as an explanation for activation by sodium sulfate 18 ; however, Bunning and Riordan 17 and Shapiro and colleagues' 9 have shown that the activation achieved by increasing the concentration of some anions appears to be a specific effect and is not due only to ionic strength. In contrast to borate, increasing concentrations of phosphate in the presence of 0.3 M NaCl increased and then decreased both human and rat serum ACE activity (Figure 1).…”
mentioning
confidence: 99%